Perspektif Islam Terhadap Aplikasi Kencan : Menyeimbangkan Teknologi Modern Dengan Nilai Budaya - Ahdini, Allifia; Duri, Cindy Rafika; Nur Pratiwi, Syifa (Bayani, 2023)
Dating App or online dating application has become a form of social interaction that is increasingly popular in today's digital era. Dating app users have a tendency to use online dating apps which often leads to unstable or temporary relationships. Basically the law of interaction carried out by the opposite sex in the view of Islam who is not a mahram, is clearly unlawful if it creates mafsadah (danger) for both of them. Making friends or making friends between the opposite gender is not a problem in Islam. But still within the limits that have been set.